The Students' Perceptions of Using Zoom Application on Mobile Phone in Improving Speaking Skills During Online Learning at Ban Loeiwangsai School, Loei Province, Thailand. - Bawanti, Putri Karya Dwi; Arifani, Yudhi (Universitas Muhammadiyah Gresik, 2021)
This study focused on the impact of using the Zoom application on mobile phones by examining students' perceptions of speaking skills and their attitude during online learning. The students have 4 months of experience using the Zoom application. This research method used a survey design and collects data by giving 12 questionnaire items through Google form to students. The participants are elementary school students with 3 categories, namely grade 4, grade 5 and grade 6 at Ban Loeiwangsai school, Thailand. The findings of this study are that the strategic design of online learning on the use of the Zoom application has an impact on students performance in independent learning and managing time. This also has an impact on the ability and knowledge of students learning English especially in the speaking skill. Their academics are particularly affected by the use of the Zoom application during online learning.